Without Parents or Pedigree: Neo-Victorian Adaptation as Disavowal or Critique - Kreilkamp, Ivan (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2013)
It has become a truism that contemporary multi-season TV dramas are inheritors of the methods and aims of Victorian serial fiction, or, as the New York Times editorial page put it in 2006, that if “Charles Dickens were alive today, he would watch The Wire, unless, that is, he was already writing for it.” While not absolutely denying the validity of such assertions, this essay reconsiders them. Sergei Eisenstein’s 1949 essay “Dickens, Griffith, and the Film Today," now a locus classicus for thinking about the links between nineteenth-century fiction and twentieth- and twenty-first-century cinematic media, first formulated a model that has remained influential for considering Victorian fiction, and especially Dickens’s novels, as offering a “pedigree” and parentage for filmic media. But through a reading of several test cases of contemporary neo-Victorian adaptation, broadly construed—including Dickensian references in The Wire, South Park’s animated Great Expectations adaptation episode, and references to George Eliot in Kazuo Ishiguru’s novel Never Let Me Go—this essay questions and complicates Eisenstein’s paradigm of the Victorian novel as parent to contemporary media.